Activity Screening of the Herb Caesalpinia sappan and an Analysis of Its Antitumor Effects. (28th June 2021) - Li, Yuan; Dong, Minghong; Wu, Zijun; Huang, Yongqi; Qian, Haibing; Huang, Cong
Abstract : Aim . Traditionally, C. sappan medicine was the heartwood, which needs to be cut down as a whole. In this research, the antitumor activity and mechanisms of the leaves and stems were compared with the roots of Caesalpinia sappan ; it was in order to investigate whether stems and leaves of C. sappan could be used to replace heartwood for antitumor treatment, thereby reducing resource destruction. Methods . MTT assays were used to identify the active sites of C. sappan based on the application of human liver cancer (HuH-7) cells. High-performance liquid chromatography (HPLC) was used to analyze polar extracts. We also established a H22 hepatoma-bearing mouse model by administering intraperitoneal injections of petroleum ether extracts from the leaves and stems (SY②) at doses of 20 and 65 mg/kg. Mice in the i.g. group were administered intragastrically with the same extracts (at doses of 100 and 325 mg/kg) at the same time (12 days). Results . The antitumor site of C. sappan was the petroleum ether extract. The IC50 for the petroleum ether extract of roots (SG②) was 56.10 μ g/ml, while that for the leaves and stems (SY②) was 77.20 μ g/ml. Grey relational analysis indicated 11 active fraction peaks that were closely related to antitumor activity. The size of tumors in H22 hepatoma-bearing mice was reduced significantly in mice administered with petroleum ether extracts from the leaves and stems (inhibition rates of high doses were 55.31% and 60.56%). Fibrous tissue proliferation, inflammatory cell infiltration, tumor cell necrosis, and the expression of proliferating cell nuclear antigen (PCNA) and vascular endothelial growth factor (VEGF) were all lower than in the control group (VEGF P < 0.001 and PCNA P < 0.05). Conclusion . Petroleum ether extracts of the roots, leaves, and stems of C. sappan exhibit certain antitumor effects. Our data indicate that the mechanisms underlying these effects may relate to a reduction in the expression of PCNA and VEGF and the inhibition of angiogenesis. Our findings indicate that we can expand the medicinal use of C. sappan to the leaves and stems, thus improving resource utilization and reducing resource damage.